Disrupsi Perpustakaan Sebagai Ruang Publik: Membedah Pemikiran Jurgen Habermas dan Ruang Publik Digital - Arienda Addis Prasetyo (Jurnal Filsafat Indonesia, 2022)
Jurgen Habermas is second generation German scientist from the Frankfurt school as well as aperson who wants to revise the thoughts of the first generations Frankfurt school figures. Histhoughts on liberation from colonialism (theoretical and social praxis), the natural sciences, social and critical sciences, the neo-Marxist spirit for change, the impasse of the first generations Frankfurt school (enlightenment dialectic) and communicative rationality in language (returning linguistics). The writing uses literature review method, primary data sources are: books and articles related to Jurgen Habermas. Then present in a descriptive narrative. There is a demand for libraries in technology development. Libraries experience a dilemma, the existence of technology will eliminate the dignity of the library as a public space, technology will have an impact on public space. The results of this study, namely: 1) the public space that was once full of liberation ideas was colonized by capitalism; 2) digital public space was born from technological developments; and 3) phenomenon in the 21st century since the birth of social media people no longer read books. In conclusion, that is the library is one of the affected public spaces. However, the challenges of the digital era, libraries must keep up with the era while still carrying out their function to provide information for users because of the function of practical scientific interests.